Sexual health dialogue between parents and teenagers: An imperative in the HIV/AIDS era - R. T. Lebese; M. Davhana - Maselesele; C. L. Obi (AOSIS, 2010)
Societies are reluctant to openly confront issues of sexuality, and this reluctance forms a barrier of communication between parents and teenagers and even between sexual partners (Wulf, 2004:2). This reluctance promotes the presence of misconceptions about sexual health, sexual risks and its consequences. Poor dialogue about sexual health between parents and teenagers is one of the contributory factors of high teenage pregnancy and sexually transmitted infection (STI) rates including HIV and AIDS. The purpose of this study was to explore and describe how dialogue about sexual health between teenagers and parents is conducted and to use the information gathered as a basis for making recommendations for improvement. A qualitative study of an explorative, descriptive and contextual nature was used. The researcher used the main question as a point of departure and more questions emanated from the discussions. There were 42 informants involved in the study, of which 4 were males and 38 were females. A purposive sampling method was used to collect data through in depth individual interviews and focus group discussions. The researcher strived to adhere to the principle of trustworthiness by adopting Guba's model (in Krefting, 1991: 217). Tech's method (Creswell, 1994: 154-55) was used to analyse the data and an independent coder was used. The results indicate that there is minimal if not absent dialogue about sexual health between teenagers and parents. Culture was identified as a major challenge to sexual health dialogue between teenagers and parents. Recommendations to enhance dialogue were made.